Social Preferences and the Variability of Conditional Cooperation - Malte Baader; Simon Gaechter; Kyeongtae Lee; Martin Sefton (Center for Economic Studies and ifo Institute (CESifo), 2022)
We experimentally examine how the incentive to defect in a social dilemma affects conditional cooperation. In our first study we conduct online experiments in which subjects play eight Sequential Prisoner's Dilemma games with payoffs systematically varied across games. We find that few second movers are conditionally cooperative (i.e., cooperate if and only if the first mover cooperates) in all eight games. Instead, most second-movers change strategies between games. The rate of conditional cooperation is higher when the own gain from defecting is lower and when the loss imposed on the first mover from defecting is higher. This pattern is consistent with both social preference models and stochastic choice models. To explore which model explains our findings we employ a second study to jointly estimate noise and social preference parameters at the individual level. The majority of our subjects place significantly positive weight on others' payoffs, supporting the underlying role of social preferences in conditional cooperation.
Keywords: A13; C91; 330; sequential prisoner's dilemma; conditional cooperation; social preferences